Pharmacological approaches in drug-resistant pediatric epilepsies caused by pathogenic variants in potassium channel genes - Filareto, Ilaria; Mosca, Ilaria; Freri, Elena; Ragona, Francesca; Canafoglia, Laura; Solazzi, Roberta; Castellotti, Barbara; Messina, Giuliana; Gellera, Cinzia; Soldovieri, Maria Virginia; Ambrosino, Paolo; Taglialatela, Maurizio; et al. (Frontiers in Cellular Neuroscience, 2025)
Variants in genes encoding for voltage-gated K+ (Kv) channels are frequent cause of drug-resistant pediatric epilepsies. Obtaining a molecular diagnosis gives the opportunity to assess the efficacy of pharmacological strategies based on in vitro features of mutant channels. In this retrospective observational study, we selected patients with drug-resistant pediatric epilepsies caused by variants in potassium channel encoding genes, followed at the Fondazione IRCCS Istituto Neurologico Carlo Besta of Milan, Italy. After the experimental characterization of variants’ functional properties in transiently transfected Chinese Hamster Ovary (CHO) cells, we identified drugs to be used as pharmacological approaches. We recruited six patients carrying different missense variants in four Kv channels (Kv7.2, Kv7.3, Kv3.1, and KNa1.1). In vitro experiments demonstrated that variants in Kv7 channels induced loss-of-function (LoF) effects, while those affecting Kv3.1 or KNa1.1 led to gain-of-function (GoF). Moreover, we found that the Kv7 channels activator gabapentin was able to revert the LoF effects caused by Kv7.2/Kv7.3 variants, and the potassium channel-blocker fluoxetine counteracted the GoF effects in Kv3.1 or KNa1.1 variants. According to experimental data, patients carrying Kv7 variants were treated with gabapentin. While this treatment resulted successful in two patients (#1, Kv7.2 G310S variant; #3, Kv7.3 V359L + Kv7.3 D542N), it resulted detrimental in the remaining case (#2, Kv7.2 D535E), requiring drug withdrawal. The application in vivo of fluoxetine to counteract GoF effects induced by Kv3.1 or KNa1.1 variants determined a significant reduction of both seizure frequency and behavior disturbances in patient #4 (Kv3.1 V425M), and in both subjects carrying KNa1.1 variants (#5, S937G and #6, R262Q). However, for the latter case, this drug was halted due to severe behavioral side effects. For most of the patients herein reported, pharmacological strategies, selected according to the in vitro functional properties of Kv-channels pathogenic variants, resulted in a significant improvement of both epileptic and cognitive features.